Bridging HFpEF Across the Care Continuum: From Screening to Phenotyping and Targeted Management - Vebiona Kartini Prima Putri; Siti Elkana Nauli; Raja Ezman Faridz Raja Shariff (Jurnal Kardiologi Indonesia, 2026)
Heart Failure with preserved Ejection Fraction (HFpEF) has become an important form of Heart Failure (HF), characterized by marked heterogeneity in pathophysiology, clinical presentation, and treatment response. It is an increasingly prevalent form of HF driven by aging populations and comorbidities such as hypertension, diabetes, obesity, and Chronic Kidney Disease (CKD). HFpEF is also associated with high morbidity, frequent hospitalizations, and diagnostic challenges, particularly in resource-limited settings. This manuscript provides a clinically focused overview of HFpEF, integrating current concepts in pathophysiology, diagnosis, phenotyping, and management. Its pathophysiology is multifactorial, involving systemic inflammation, endothelial dysfunction, myocardial stiffness, and contributions from comorbid conditions. Emerging evidence highlights the roles of adiposity and inflammatory pathways, reinforcing the view of HFpEF as a multisystem disorder rather than purely a cardiac condition. The condition is also markedly heterogeneous, with several phenotypes identified, including cardiometabolic, obesity-related, cardiorenal, chronotropic incompetence, and Atrial Fibrillation (AF)–associated HFpEF. These phenotypes influence disease progression and therapeutic response. Additionally, numerous clinical mimics, such as pulmonary disease, valvular heart disease, and infiltrative cardiomyopathies, complicate diagnosis. Diagnosis requires a structured, probability-based approach combining clinical assessment, biomarkers, echocardiography, and, when necessary, stress testing or invasive hemodynamics. However, limited access to advanced diagnostics necessitates pragmatic, tiered approaches, especially in low-resource settings. Management focuses on three pillars: optimization of comorbidities, guideline-directed medical therapy, and phenotype-specific treatment strategies. While no therapy conclusively reduces mortality, recent advances have improved symptom control and hospitalizations. Overall, HFpEF demands a holistic, individualized approach integrating pathophysiology, clinical phenotyping, and healthcare system constraints to improve patient outcomes.